2020
DOI: 10.1111/asj.13327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delaying post‐hatch feeding on lipid peroxidation and antioxidant enzyme mRNA expression in the pectoralis major muscle of newly hatched chicks

Abstract: Newly hatched chicks contain residual yolk in their abdominal cavity, which supplies them with nutrients; however, this residual yolk is insufficient to meet the nutritional requirements for both maintenance and growth (Bigot, Tesseraud, Taouis, & Picard, 2001). Thus, many researchers suggest that early exogenous nutrients are important for body growth and skeletal muscle growth in newly hatched chicks (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Adding 300 mg/kg resveratrol to the diet of finishing pigs could reduce the level of malondialdehyde in the longissimus muscle and increase the activity of SOD and SOD2 mRNA levels [ 82 ]. The results revealed that the lipid peroxidation level of delayed-feeding chicks was higher than that of free-feeding chicks (free-feeding after hatching), and the mRNA expression of Cu/Zn-SOD, Mn-SOD and GPX7 in delayed-feeding chicks (delayed-feeding chicks from 0 to 2 days of age) was lower than that of free-feeding chicks, but there was no difference in catalase mRNA level [ 83 ]. This indicated that delayed post-incubation-feeding affected the lipid peroxidation of muscle during the growth of chicks.…”
Section: The Application and Research Status Of Sods In Medicine Food...mentioning
confidence: 99%
“…Adding 300 mg/kg resveratrol to the diet of finishing pigs could reduce the level of malondialdehyde in the longissimus muscle and increase the activity of SOD and SOD2 mRNA levels [ 82 ]. The results revealed that the lipid peroxidation level of delayed-feeding chicks was higher than that of free-feeding chicks (free-feeding after hatching), and the mRNA expression of Cu/Zn-SOD, Mn-SOD and GPX7 in delayed-feeding chicks (delayed-feeding chicks from 0 to 2 days of age) was lower than that of free-feeding chicks, but there was no difference in catalase mRNA level [ 83 ]. This indicated that delayed post-incubation-feeding affected the lipid peroxidation of muscle during the growth of chicks.…”
Section: The Application and Research Status Of Sods In Medicine Food...mentioning
confidence: 99%
“…In our previous studies, delayed feeding for 48 h resulted in the reduced expression of Cu/Zn-SOD and Mn-SOD mRNA levels, which also resulted in increased plasma and muscle lipid peroxidation[ 7 , 10 ]. In this study, the metabolic pathway analysis of the metabolomic data indicated that delayed feeding resulted in changes in glutathione metabolism, a pathway that plays an important role in antioxidant defense[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed feeding also alters the expression of genes associated with protein metabolism[ 8 , 9 ]; for example, FBXO32 mRNA expression increased after 48 h of delayed feeding. In another previous study, we reported that 48 h of delayed feeding reduced the mRNA levels of Cu/Zn-SOD and Mn-SOD and consequently increased lipid peroxidation levels in the skeletal muscle and plasma of chicks at 13 days post hatch[ 10 ]. These results suggest that delaying post-hatch feeding may affect several metabolic pathways in chicks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation